Chemical Composition of Urtica simensis Grown in Different Regions of Ethiopia. (30th March 2020) - Bayba, Koju Bedekach; Dubale, Amare Aregahegn; Mehari, Bewketu; Atlabachew, Minaleshewa
Abstract : Leaf samples of Urtica simensis collected from different locations of Ethiopia were analyzed for their proximate compositions, total phenolic and flavonoid contents, antioxidant activities, and fatty acid profiles. The proximate analysis results revealed the presence of ash in the range 17.2–24.3%, crude fat 3.19–3.50%, crude protein 3.42–6.38%, crude fiber 9.37–14.0%, and carbohydrate 56.7–63.7%. The determined total polyphenols, flavonoids, and antioxidant activities ranged 2.18–4.84 mg gallic acid, 1.35–4.46 mg catechin, and 1.58–3.36 mg ascorbic acid, respectively, equivalents per gram of dry sample. High variability was observed for polyphenol and flavonoid contents while only random variation was observed for crude fat and carbohydrate among samples from different locations. In addition, the fatty acid profiles of the leaves were analyzed by using gas chromatography coupled with mass spectrometry. A total of 16 different fatty acids were detected in the samples. Linolenic, palmitic, and linoleic acids were the major fatty acids with average compositions of 36.6, 20.7, and 15.5%, respectively, of the total fatty acid. The result of this study revealed that the carbohydrate and ash contents of leaves of Urtica simensis are exceptionally high to make the leaves a significant source of the dietary important chemicals. Additionally, the lipid fraction of the leaves was found to be rich in essential fatty acids ( α -linolenic and linoleic acids) that are critically required in the human diet.